La Poesia Visiva (1963-1979) : (1963-1979) La Poesia Visiva - Dorfles, Gillo; Fagone, Vittorio; Menna, Filiberto; Migliorini, Ermanno; Ori, Luciano (Firenze : Vallecchi, 1979)
Isgro, Emilio ; La Rocca, Ketty ; Marcucci, Lucia ; Miccini, Eugenio ; Ori, Luciano ; Perfetti, Michele ; Pignotti, Lamberto ; Vaccari, Franco ; etc.
La Poesia Visiva (1963-1979) : (1963-1979) La Poesia Visiva, Sala d'Arme di Palazzo Vecchio, Firenze, 15 dicembre 1979 - 12 gennaio 1980
boek